Dosimetry audit for megavoltage photon beams applied in non-reference conditions - Ahmad Fadzil, Muhammad Safwan (Elsevier, 2022)
Purpose : We have conducted for the first time a Malaysian postal dosimetry audit of external beam under non-reference conditions by evaluating the output performance while screening for systematic errors within the dosimetry chain. The potential use from the choice of detector were investigated along with the search for other sources of discrepancies. Methods ; Ten radiotherapy centres were audited, encompassing 16 megavoltage photon beam arrangements, adopting the IAEA postal dosimetry protocol for non-reference conditions, with a holder modified to accommodate three TLD types: Ge-doped cylindrical silica fibres (CF), Ge-doped flat silica fibres (FF), and TLD-100 powder. Results : Eight of the centres operated within ± 5% of stated dose, one other exceeding tolerance for all measured points, and one did not return any dosimeters for analysis after failing the initial irradiations. Post remedial measures, the mean relative response for CF, FF, and TLD-100 was 1.00, 0.99, and 0.98 respectively, with associated coefficients of variation 6.87%, 6.45%, and 5.06%. Conclusion : High quality radiotherapy clinical practice postal dosimetry audits that are based on sensitive TLDs are seen to be particularly effective in identifying and resolving dose delivery discrepancies.